2011
DOI: 10.1007/s11916-011-0225-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise and Physical Activity on Knee Osteoarthritis

Abstract: Exercise is one of the most discussed and controversial nonpharmacologic management strategies for osteoarthritis (OA) of the knee. Health care providers and patients share varied and often pseudoscientific beliefs regarding the effects of exercise on knee OA formulated on outdated notions of the etiology, pathophysiology, and progression of the condition. Based on the contemporary literature, regular light to moderate physical activity has both preventive and therapeutic benefits for individuals with knee OA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 74 publications
(64 reference statements)
1
51
0
Order By: Relevance
“…34 Specifically, OA patients have shown a significant decrease in pain, [23][24][25][26][27][28] a reduction in joint stiffness, 26,27 an increase in joint range of motion, 28 and an improvement in functional performance 23,26 following NMES training. Although we cannot establish a direct causative association between muscle strength and health status, stronger knee extensor muscles are thought to decrease impact forces at the knee joint, 16,17 and might reduce the mechanical stimuli for pain, 18 thereby relieving the pain symptoms of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…34 Specifically, OA patients have shown a significant decrease in pain, [23][24][25][26][27][28] a reduction in joint stiffness, 26,27 an increase in joint range of motion, 28 and an improvement in functional performance 23,26 following NMES training. Although we cannot establish a direct causative association between muscle strength and health status, stronger knee extensor muscles are thought to decrease impact forces at the knee joint, 16,17 and might reduce the mechanical stimuli for pain, 18 thereby relieving the pain symptoms of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging in a physically active lifestyle delays disability and promotes OA-specific benefits, including maintaining physical function and decreasing pain, depression, and fatigue (3)(4)(5)(6). Physical activity has been shown to delay the progression of OA and of functional limitations (7).…”
Section: Introductionmentioning
confidence: 99%
“…Esser and Bailey [11] concluded that exercising can be a powerful medicine for patients with knee OA. Carvalho et al [5] found that home exercising (printed manual) with monthly reassessment by physiotherapist allowed in patients with knee OA to achieve a significant improvement in pain, knee ROM during flexion, muscle strength and functional capacity.…”
Section: Discussionmentioning
confidence: 99%